1998
DOI: 10.1006/viro.1998.9127
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Hepatitis C Virus Infection to Tree Shrews

Abstract: Although hepatitis C virus (HCV) infection can be reproduced in chimpanzees, these animals are rare and expensive. Tree shrews (tupaias) are small animals, closely related to primates, which adapt easily to a laboratory environment. In this work we have investigated the susceptibility of Tupaia belangeri chinensis to HCV infection. Tupaias caught in the wild in Yunnan (China) were inoculated in China with HCV genotype 1b (study A) and in Spain with a mixture of genotypes 1b, 1a, and 3 (study B). In study B tup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 22 publications
2
82
0
1
Order By: Relevance
“…Tupaia belangeri has been shown to be susceptible to infection with a variety of human viruses, including rotavirus, herpes simplex virus, and hepatitis B and C viruses. [21][22][23][24] We and others have demonstrated that primary Tupaia hepatocytes (PTHs) represent a convenient and suitable in vitro model to study HBV infection and replication. [25][26][27] In this study, we demonstrate that HBV core promoter mutants associated with fulminant hepatitis exhibit a phenotype in primary hepatocytes distinctly different from previous findings in hepatoma cell lines.…”
mentioning
confidence: 99%
“…Tupaia belangeri has been shown to be susceptible to infection with a variety of human viruses, including rotavirus, herpes simplex virus, and hepatitis B and C viruses. [21][22][23][24] We and others have demonstrated that primary Tupaia hepatocytes (PTHs) represent a convenient and suitable in vitro model to study HBV infection and replication. [25][26][27] In this study, we demonstrate that HBV core promoter mutants associated with fulminant hepatitis exhibit a phenotype in primary hepatocytes distinctly different from previous findings in hepatoma cell lines.…”
mentioning
confidence: 99%
“…To increase the susceptibility of tupaia to hCV infection and to develop a sensitive hCV infection model, these differences between hCV infection in tupaias and humans should be examined in future. hCV infection studies in tupaias have been examined using x-rays [41] and metabolic analysis [31], and the efficacy of natural products for treating hCV-infected tupaia has also been evaluated [39]. several groups have successfully infected tupaias with hBV, as follows.…”
Section: Tupaia As Viral Hepatitis Modelmentioning
confidence: 99%
“…Interestingly, the tree shrew Tupaia belangeri can be infected by HCV, although the viral titres remain low (Amako et al, 2010;Xie et al, 1998;Xu et al, 2007;Zhao et al, 2002). HCV-infected tree shrews produce infectious viral particles and, interestingly, can develop chronic hepatitis leading to fibrosis and cirrhosis (Amako et al, 2010).…”
Section: Chimpanzee Model: Adaptive Immune Responsesmentioning
confidence: 99%